Increased myocellular lipid and IGFBP‐3 expression in a pre‐clinical model of pancreatic cancer‐related skeletal muscle wasting. Issue 3 (7th May 2021) - Cole, Calvin L.; Bachman, John F.; Ye, Jian; Murphy, Joseph; Gerber, Scott A.; Beck, Christopher A.; Boyce, Brendan F.; Muthukrishnan, Gowrishankar; Chakkalakal, Joe V.; Schwarz, Edward M.; Linehan, David
Abstract: Background: Skeletal muscle wasting (SMW) in cancer patients is associated with increased morbidity, mortality, treatment intolerance and discontinuation, and poor quality of life. This is particularly true for patients with pancreatic ductal adenocarcinoma (PDAC), as over 85% experience SMW, which is responsible for ~30% of patient deaths. While the established paradigm to explain SMW posits that muscle catabolism from systemic inflammation and nutritional deficiencies, the cause of death, and the cellular and molecular mechanisms responsible remain to be elucidated. To address this, we investigated the relationship between tumour burden and survival in the KCKO murine PDAC model. Methods: Female C57BL/6J mice 6–8 weeks of age underwent orthotopic injection with KCKO‐luc tumour cells. Solid tumour was verified on Day 5, post‐tumour inoculation. In vivo, longitudinal lean mass and tumour burden were assessed via dual‐energy X‐ray absorptiometry and IVIS imaging, respectively, and total body weight was assessed, weekly. Animals were sacrificed at a designated end point of 'failure to thrive'. After sacrifice, lower limb hind muscles were harvested for histology and RNA extraction. Results: We found a strong correlation between primary tumour size and survival ( r 2  = 0.83, P  < 0.0001). A significant decrease in lower limb lean mass was first detected at Day 38 post‐implantation vs. no tumour controls (NTCs) ( P  < 0.0001). SMW was confirmed by histology, which demonstrated a 38%, 32.7%, and 39.9% decrease in fibre size of extensor digitorum longus, soleus, and tibialis anterior muscles, respectively, in PDAC mice vs. NTC ( P  < 0.002). Histology also revealed a 67.6% increase in haematopoietic cells within the muscle of PDAC mice when compared with NTC. Bulk RNAseq on muscles from PDAC mice vs. NTC revealed significant increases in c/ebpβ/Δ, il‐1, il‐6, and tnf gene expression. Pathway analyses to identify potential upstream factors revealed increased adipogenic gene expression, including a four‐fold increase in igfbp‐ 3. Histomorphometry of Oil Red‐O staining for fat content in tibialis anterior muscles demonstrated a 95.5% increase in positively stained fibres from PDAC mice vs. NTC. Conclusions: Together, these findings support a novel model of PDAC‐associated SMW and mortality in which systemic inflammation leads to inflammatory cell infiltration into skeletal muscle with up‐regulated myocellular lipids.